Substance P-immunoreactive axon innervation of mouse stomach - Nguyen, Duyen; Mistareehi, Anas; Ma, Jichao; Madas, Jazune; Kwiat, Andrew M; Bendowski, Kohlton; Chen, Jin; Li, De-Pei; Furness, John; Powley, Terry L; Cheng, Zixi (SPARC Portal, 2022)
Immunohistochemistry revealed the morphology and distribution of nociceptor Substance P-immunoreactive (SP-IR) axons and terminals in the muscular layers (longitudinal muscle, myenteric plexus, and circular muscle) of the mouse stomach.